2014
DOI: 10.1021/bi500648n
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intermediates in the Oxidative Half-Reaction of the FAD-Dependent Thymidylate Synthase fromThermotoga maritima: Carbon Transfer without Covalent Pyrimidine Activation

Abstract: Thymidylate, a vital DNA precursor, is synthesized by thymidylate synthases (TSs). A second class of TSs, encoded by the thyX gene, is found in bacteria and a few other microbes and is especially widespread in anaerobes. TS encoded by thyX requires a flavin adenine dinucleotide prosthetic group for activity. In the oxidative half-reaction, the reduced flavin is oxidized by 2′-deoxyuridine 5′-monophosphate (dUMP) and (6R)-N5,N10-methylene-5,6,7,8-tetrahydrofolate (CH2THF), synthesizing 2′-deoxythymidine 5′-mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(64 citation statements)
references
References 38 publications
4
60
0
Order By: Relevance
“…A new mechanism for dUMP activation based on ionization of N3 follows from a modification of the mechanism 6 shown in Figure 1B. The negative charge of the ionized nitrogen produced when dUMP binds FDTS delocalizes onto O2 and O4 (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A new mechanism for dUMP activation based on ionization of N3 follows from a modification of the mechanism 6 shown in Figure 1B. The negative charge of the ionized nitrogen produced when dUMP binds FDTS delocalizes onto O2 and O4 (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant WT and mutagenized FDTSs from T. maritima were purified as previously reported, 6 followed by formation of apo-protein by treatment with concentrated sodium chloride 10 and reincorporation of exogenous FAD after desalting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectrophotometric studies have shown noticeable changes in the ultraviolet–visible (UV–vis) absorption spectra and the presence of reaction intermediates for the Tm FDTS catalyzed formation of dTMP (oxidative half-reaction; Fig. 3) [15,34,35]. Under anaerobic conditions, addition of either substrate, dUMP or CH 2 H 4 folate, to reduced enzyme first leaves the UV–vis spectrum relatively unchanged, however addition of the second substrate significantly changes the absorbance of the FDTS complex (black trace in Fig.…”
Section: Kinetic Considerationsmentioning
confidence: 99%